(untitled) (Journal of Business and Technology (Dhaka), 2012)
This paper is an endeavor to depict the conditions of the female workers from two perspectives. One is social perspective and the other is economic perspective. The analysis is based on the survey of 151 female workers of 29 garment industrial units located in different parts of Chittagong Metropolitan area. This study suggests that the standard of living of the female garment workers is still in precarious condition and they are not free from the vicious circle of poverty and face extreme difficulties in obtaining their basic needs for survival even. This paper recommends measures for improving the prevailing socio-economic facilities, to a great extent, to achieve female workers’ satisfaction at the maximum level. Key Words: Female Garments Workers; Social Factors; Economic Factors. DOI: http://dx.doi.org/10.3329/jbt.v5i2.9935 Journal of Technology (Dhaka) Vol. 5(2), July-December, 2010 53-70